Reciprosity and Cooperation in Repeated Coordination Games: The Blurry Belief Approach - Alvaro Sandroni (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
Two long lived players play a repeated coordination game. Players do not specify a single (and correct) probability to each event. They have a vague notion about the evolution of the play, called blurry beliefs, which guide their behavior. General conditions that ensure cooperation are investigated. Key words: Repeated Games, Learning, Cooperation, Bounded Rationality, Equilibrium Selection.
Keywords: D83; 330